Detection and treatment of skin infection with Staphylococcus aureus in children with atopic dermatitis - O.V. Mozyrska (Group of Companies Med Expert, LLC, 2023)
Introduction. Atopic dermatitis is a common chronic relapsing inflammatory multifactorial skin disease. Staphylococcus aureus skin colonization increases during disease outbreaks and correlates with the severity of skin symptoms. Purpose - to evaluate the effectiveness of thyrothricin gel as an adjuvant therapy in the treatment of atopic dermatitis and the influence of polymorphisms of pattern recognition receptors on the achieving a therapeutic effect. Materials and methods. This study included patients with atopic dermatitis (n=37) aged 2-18 years from the Allergy Department of the Kyiv City Children's Clinical Hospital No. 2. Patients were devided into two groups: a group that received thyrothricin gel on the affected skin areas 2 times a day for 7 days (the Group A) and a control group (the Group B) that received only basic symptomatic therapy. SCORAD (SCORing AD) and CDLQI (Children's Quality of Life Index in Dermatology) scores were recorded before and after treatment, side effects were recorded during the study. Skin swabs were taken in the Group A before and after treatment. Genotyping of polymorphisms rs4696480 in the TLR2 gene, rs7309123 in the Dectin-1 gene were performed using polymerase chain reaction. Results. In both groups of children, improvement was observed in 7 days after treatment (p<0.001). In the Group A, the improvement in ΔSCORAD was 16.6±5.9 points, in the Group B - 8.1±4.5 points. The difference in ΔSCORAD scores between the Groups A and B was statistically significant (W=225.0, p<0.001). The decrease in CDLQI score after treatment was 3.8±1.8 points in the Group A and 2.3±1.25 points in the Group B. A significant decrease in CDLQI score was demonstrated in the intervention group than in the control group after treatment (W=275.5, p=0.004). After treatment, a bacteriological examination of the skin demonstrated the eradication of Staphylococcus aureus: in the Group A, 94.4% of patients were Staphylococcus aureus-negative. Polymorphisms rs4696480 in the TLR2 gene and rs7309123 in the Dectin-1 gene did not affect the speed of achieving the therapeutic effect. Conclusions. The addition of thyrothricin to standard therapy for atopic dermatitis in children with Staphylococcus aureus infection of affected skin may provide significant clinical benefit in SCORAD and CDLQI scores. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patients was obtained for conducting the studies. No conflict of interests was declared by the author.